Change Management Framework: Development Curriculum of Islamic Education at School - Ahmad Muslih Atmojo; Djamaluddin Perawironegoro; Khoirul Umam (Indonesian Journal of Education and Social Studies, 2022)
The purpose of this study was to analyze how the concept of change management from PAI curriculum development at SMP Muhammadiyah 1 Gamping. The method used in this research is field research which was developed with a qualitative approach model. Called field research because the data that the authors collect comes from the field. Curriculum development itself is related to the preparation of all dimensions of the curriculum, starting from the foundation, the structure of the composition of subjects, the scope, the sequence of learning materials, the outline of the learning program, to the development of implementation guidelines. In addition, curriculum development is a planning process, resulting in better tools based on the results of the current curriculum assessment, to provide better teaching in learning conditions. This means that curriculum development is an activity to produce a new curriculum through the preparation of the curriculum itself or the basis of the results of the assessment carried out within a certain period. Therefore, it is important to evaluate and develop curriculum changes accurately to the existing educational process to achieve common and comprehensive goals, including what happened and was done by SMP Muhammadiyah 1 Gamping.